Associations of multiple trace elements with bipolar disorder in adolescents: A case-control study - Jie Li; Xuemei Li; Yuqian He; Yajie Huang; Wenjing Wang; Hang Du; Chengzhi Chen; Dan Zhu; Xinyu Zhou (PLoS ONE, 2025)
Background Bipolar disorder (BD) is a serious mental disorder. Studies have shown an association between trace elements and mental disorders. However, this association has not been thoroughly studied in adolescents with BD. We aimed to investigated the associations between multiple trace elements and adolescent BD. Method This case-control study included 144 BD patients with BD and 144 matched controls. Seventeen elements in the participants’ urine were measured using inductively coupled plasma mass spectrometry (ICP-MS). Least absolute shrinkage and selection operator (LASSO), multivariate logistic regression, restricted cubic spline (RCS), and Bayesian kernel machine regression (BKMR) were used to analyze the association between exposure to single and mixed elements and adolescent BD. Results In the single-element models, titanium, manganese, rubidium, and iodine were negatively associated with adolescent BD. In the multi-element model selected by LASSO, titanium (OR = 0.14, 95% CI: 0.04–0.53), manganese (OR = 0.02, 95% CI: 0.01–0.08), and iodine (OR = 0.06, 95% CI: 0.02–0.22) showed a negative correlation with adolescent BD, while magnesium (OR = 11.24, 95% CI: 1.83–69.12), and nickel (OR = 6.86, 95% CI: 1.55–30.29) displayed a positive correlation. The RCS results showed a non-linear correlation between the elements titanium, manganese, iodine, magnesium, nickel, zinc, strontium and adolescent BD. In addition, the BKMR analysis showed a significant joint effect of multiple elements on adolescent BD when the concentrations of the seven elements were at or above the 55th percentile, compared with their median values. Conclusions Our findings revealed that urinary titanium, manganese, and iodine were negatively correlated with adolescent BD, whereas urinary magnesium and nickel were positively correlated with adolescent BD. These results provide evidence of an association between urinary trace elements and adolescent BD.